769 EFFECT OF GLUCOSE LOWERING AGENTS ON CARDIAC AUTONOMIC FUNCTION AND STRUCTURE IN TYPE 2 DIABETES MELLITUS. (15th December 2022) - Veneziano, Francesco Antonio; Cavallari, Ilaria; Grigioni, Francesco; Tuccinardi, Dario; Maddaloni, Ernesto; Indennidate, Carla; Pieralice, Silvia; Napoli, Nicola; Buzzetti, Raffaella
Abstract : : Effects of novel glucose-lowering agents on cardiac autonomic function and structure in type 2 diabetes Ilaria Cavallari, Ernesto Maddaloni, Francesco Veneziano, Carla Indennidate, Maria Valeria Giaccari, Dario Tuccinardi, Silvia Pieralice, Nicola Napoli, Raffaella Buzzetti, Francesco Grigioni Background: Novel glucose-lowering agents, such as sodium glucose co-transporter-2 (SGLT-2) inhibitors and glucagon-like peptide-1 (GLP-1) receptor agonists, have the potential to reduce major adverse cardiovascular events among people with type 2 diabetes. However, mechanisms behind their cardiovascular protection and the implications of positive chronotropic effects of GLP-1 receptor agonists are not fully understood. Purpose: To elucidate and compare the effects of novel glucose-lowering agents on cardiac autonomic function and structure. Methods: This prospective observational study included subjects with type 2 diabetes and either a history of established cardiovascular disease or multiple risk factors and early initiation (within 2 weeks) of a SGLT-2 inhibitor or a GLP-1 receptor agonist on top of standard of care. Patients were followed for a median of 2 months. As per study protocol, background medical therapy should have remained stable for the entire duration of the study. Cardiac autonomic reflex tests (heart rate response to a deep breathing and to standing) and echocardiography were performed in all patients at baseline and at the end of follow-up. Endpoints were changes from baseline of E/I ratio, 30:15 ratio and indices of cardiac structure and function. Results: A total of 37 patients completed follow-up, of whom 20 were on SGLT-2 inhibitors and 17 on GLP-1 receptor agonists. Mean age was 69 years, mean disease duration was 14 years and mean HbA1c value was 7.5%. Cardiac autonomic dysfunction, defined as at least an abnormal test, was found in 19% of patients (n=7). At a median follow-up of 2 months, there were no differences from baseline in heart rate response to a deep breathing test (p=0.92) and to standing (p=0.86). No differences were found when patients were stratified according to drug class. Among echocardiographic parameters, significant reductions of left ventricular mass (300.5±73.3 vs 280.4±68.3 g/m 2, p=0.048) and left atrial volume (61.3±29.4 vs 54.7±18.0 ml, p=0.034) were found with no interaction by drug class. Left ventricular end-diastolic and systolic volumes, ejection fraction, filling pressures and pulmonary artery pressure did not substantially change. Conclusions: In a population of patients with type 2 diabetes, short-term treatment with novel glucose-lowering agents significantly reduced left ventricular mass and left atrial volume but did not affect cardiac autonomic function.